2019
DOI: 10.1002/sscp.201800140
|View full text |Cite
|
Sign up to set email alerts
|

Presence of benzotriazoles, benzothiazoles and benzenesulfonamides in surface water samples by liquid chromatography coupled to high‐resolution mass spectrometry

Abstract: An analytical method has been developed for the simultaneous determination of seven benzotriazole, five benzothiazole and four benzenesulfonamide derivatives in surface water samples. The procedure is based on solid‐phase extraction with Oasis HLB, followed by high‐performance liquid chromatography coupled to high‐resolution mass spectrometry. Apparent recoveries ranged from 40 to 101%, except for compounds the matrix effect of which was above ‐60%. The repeatability (n = 5) of the method was below 20% for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
2
11
1
Order By: Relevance
“…Benzothiazole (C7H5NS) belongs to a class of structurally similar molecules called benzothiazoles, which are a group of high production volume chemicals found in wastewater and urban runoff (De Wever and Verachtert, 1997;Hidalgo-Serrano et al, 2019). Based on analysis in Franklin et al (2021) where the benzothiazole molecule was (1) consistently observed in significant quantities in the dissolved, gas, and aerosol phases, (2) the gas-phase molecule displayed temporal behavior similar to a group of other anthropogenic gases, and (3) anthropogenic benzothiazole tracer species were observed, we attribute its source as primarily anthropogenic from the presence of pollutants in coastal waters.…”
Section: Gas-phase Sulfur Budget During Bloommentioning
confidence: 99%
“…Benzothiazole (C7H5NS) belongs to a class of structurally similar molecules called benzothiazoles, which are a group of high production volume chemicals found in wastewater and urban runoff (De Wever and Verachtert, 1997;Hidalgo-Serrano et al, 2019). Based on analysis in Franklin et al (2021) where the benzothiazole molecule was (1) consistently observed in significant quantities in the dissolved, gas, and aerosol phases, (2) the gas-phase molecule displayed temporal behavior similar to a group of other anthropogenic gases, and (3) anthropogenic benzothiazole tracer species were observed, we attribute its source as primarily anthropogenic from the presence of pollutants in coastal waters.…”
Section: Gas-phase Sulfur Budget During Bloommentioning
confidence: 99%
“…MeSH is the major DMSP d product (∼ 75 % yield) and is formed when bacteria demethylate or demethiolate DMSP d (Kiene, 1996;Kiene and Linn, 2000b). However, existing measurements of dissolved MeSH concentrations are significantly smaller than collocated dissolved DMS concentrations (< 1.8 nM versus < 6 nM) (Kettle et al, 2001). This is a result of its reaction with dissolved organic matter and its rapid incorporation into bacterial cells where it is used to form methionine (Flöck and Andreae, 1996;Kiene, 1996;Kiene et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations in the available sulfur pool and bacterial sulfur demand can translate to significant variability in waterside measurements of DMS : MeSH over the open ocean. In upwelling regions of the Atlantic Ocean, waterside DMS : MeSH has been shown to range between 1 and 30 (Kettle et al, 2001). Measurements made in the Baltic Sea, Kattegat-Skagerrak, and North Sea have shown waterside DMS : MeSH of 16, 20, and 6, respectively (Leck and Rodhe, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of any xenobiotic compounds in fresh, ground, or marine water represents a threat to organisms living in these ecosystems and, therefore, to human health. Among organic pollutants, a group of high production volume chemicals, benzotriazole (BTRs), benzothiazoles (BTs), and benzenesulfonamides (BSAs), benzo-fused nitrogen heterocyclic compounds containing a benzene ring, has been used for several decades in a large number of industrial activities and consuming products [1].…”
Section: Introductionmentioning
confidence: 99%
“…BSAs are used for synthesizing dyes, photo-chemicals, disinfectants, and intermediates in the production of pharmaceuticals [7,8]. These polar compounds, some of them resistant to biodegradation, can constitute an environmental threat due to their widespread application and consequent ubiquitous occurrence in various environmental compartments [1,7]. growth, and is considered a good indicator to evaluate the toxicity of contaminants present in marine water.…”
Section: Introductionmentioning
confidence: 99%